Evaluation of germ plasm for resistant to Soybean mosaic virus (SMV) - Wuye Ria Andayanie (Universitas Merdeka Madiun, 2020)
Soybean superior varieties with high yields and are resistant to abiotic stress have been largely released, although some varieties grown in the field are not resistant to SMV. In addition, the opportunity to obtain lines of hope as prospective varieties with high yield and resistance to SMV is very small. The method for evaluating soybean germplasm is based on serological observations of 98 accessions of leaf samples from SMV inoculation with T isolate. The evaluation results of 98 accessions based on visual observations showed 31 genotypes reacting very resistant or healthy to mild resistant category to SMV T isolate with a percentage of symptom severity of 0 −30 %. Among 31 genotypes there are 2 genotypes (PI 200485; M8Grb 44; Mlg 3288) with the category of visually very resistant and resistant, respectively and Mlg 3288 with the category of mild resistant. They have a good agronomic appearance with a weight of 100 seeds (˃10 g) and react negatively with polyclonal antibodies to SMV, except Mlg 3288 reaction is not consistent, despite the weight of 100 seeds (˃ 10 g). Leaf samples from 98 accessions revealed various symptoms of SMV infection in the field. This diversity of symptoms is caused by susceptibility to accession, when infection occurs, and environmental factors. Keywords—: soybean; genotipe; Soybean mosaic virus (SMV); disease severity; polyclonal antibody